The complete genome of a putative endornavirus identified in yerba mate (Ilex paraguariensis St. Hil.) - Debat, Humberto Julio; Grabiele, Mauro; Aguilera, Patricia Mabel; Bubillo, Rosana Elizabeth; Zapata, Pedro Darío; Marti, Dardo Andrea; Ducasse, Daniel Adrian (2018)
We present the first report of a virus infecting the subtropical tree crop yerba mate (Ilex paraguariensis St. Hil.). Total RNA purification, followed by next-generation sequencing, transcripts assembly and annotation, resulted in the identification of a new endornavirus species infecting yerba mate. The complete sequence of the linear dsRNA viral genome is 13,954-nt long, contains a single 13,743 nt ORF, and presents a 149 nt 5′UTR and a 61 nt 3′UTR. The predicted ORF encodes a 4,581 aa polypeptide with a UDP-glucose glycosyl-transferase, a capsular polysaccharide synthesis protein, and a RNA-dependent RNA polymerase domain. The name yerba mate endornavirus is proposed for the identified virus. Due to the intriguing peculiarities of this virus family, and the complete lack of the yerba mate virus literature, we consider that the information reported here will be helpful in leading to a new and needed attention to this important topic and crop.